Extended tacrolimus release via the combination of lipid-based solid dispersion and HPMC hydrogel matrix tablets - Hui Xu; Li Liu; Xuehui Li; Junyuan Ma; Rui Liu; Shaoning Wang (Elsevier, 2019)
The objective of this study is to evaluate the feasibility of obtaining extended release of tacrolimus by a novel combination of lipid-based solid dispersion and matrix-type extended release tablet techniques. Tacrolimus solid dispersion was prepared using glycerylbehenate (Compritol® ATO888) and Pluronic F127 as the carrier materials with hot-melt method, which was then blended with hydrogel matrix materials, such as HPMC and lactose, the powders were directly compressed into tablets. In vitro drug release tests were carried out to evaluate the performance of the solid dispersions and the tablets. The dissolution rate of tacrolimus was significantly improved by the lipid-based solid dispersion, and the incorporation of HPC into the solid dispersion obviously improved its stability after storage. Extended release tablets loaded with tacrolimus solid dispersion showed prolonged drug release patterns over 24 h, the release patterns of the tablets can be tailored by the compositions of the matrix materials, including the types and content of HPMCs. A modified processing method that directly mixed the melted solid dispersion with HPMC powders improved the uniformity of the solid dispersion inside the tablet matrix and release profile. The release data of the extended release tablet fitted well to the Korsmeyer-Peppas model with n value of 0.85, which suggested diffusion- and erosion-controlled release mechanism. The combination of lipid-based solid dispersion and HPMC hydrogel matrix may find wide applications in the extended release dosage forms of high potent, water-insoluble drugs. Keywords: Tacrolimus, Solid dispersion, Lipid, Extended-release tablet